Bulk Soil Electrical Conductivity for Coastal Salt Affected Soils of West Bengal - MANDAL, UTTAM KUMAR; BURMAN, D.; MAHANTA, K. K.; SARANGI, SUKANTA; RAUT, SHISHIR; MANDAL, SUBHASIS; MAJI, B.; BANDYOPADHYAY, B. K. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
Soil salinization is of great concern in the irrigated arid, semiarid and coastal region due to its threat to sustainable agricultural productivity and thus there is need to closely monitor it. The measurement of electrical conductivity (EC) in saturated paste extracts (ECe) is the standard to which other salinity estimation methods are referenced. Since this method is laborious, the preparation of saturated pastes subject to bias, and salinity estimates by EC subject to chemical artefact, we evaluated the performance of an EC probe for measuring bulk soil EC. A calibration curve was developed between bulk soil EC and EC in saturation paste for coastal soils of West Bengal (r2 = 0.942). The bulk soil EC probe was used to measure the depth-wise soil salinity in conservation tillage experiment and it was found that no till plot was comparatively more saline than conventional and reduced tillage treatments. The bulk soil EC probe is a quick, reliable, easy to take soil measurement for the spatio-temporal characterization of soil salinity.